Detecting recurrent ovarian cancer: revisit the values of whole-body CT and serum CA 125 levels. (October 2019) - Wang, Pieh-Hsu; Huang, Yu-Ting; Ng, Koon-Kwan; Chou, Hung-Hsueh; Lu, Hsin-Ying; Ng, Shu-Hang; Lin, Gigin
Background: Computed tomography (CT) has served as the first-line imaging modality but its role for detecting recurrent ovarian cancer should be revisited in the era of whole-body CT. Purpose: To study anatomical distributions and imaging patterns of recurrent ovarian epithelial cancer through whole-body CT and their associations with serum cancer antigen 125 (CA 125) levels. Material and Methods: This retrospective study approved by the institutional review board comprised a cohort of 497 patients with ovarian cancer. The specific anatomical locations and imaging features of recurrent lesions on CT at the time of recurrence were analyzed. Results: Fifty-nine patients had ovarian cancer recurrence. The median time from diagnosis to recurrence was 17 months (range = 8–51). Among the 144 recurrent lesions, the leading recurrent sites were the intraperitoneal cavity and lymph nodes. Cystic lesions were significantly more frequently located intraperitoneally ( P = 0.026), in particular with locoregional recurrence ( P = 0.006). Serum CA 125 levels in the patients were significantly higher in the presence of peritoneal metastases ( P = 0.010), locoregional lesions at the cul-de-sac or vaginal stump ( P = 0.002), and metastases to infradiaphragmatic organs ( P = 0.013). Among the 18 patients with CA 125 levels ≤ 35 U/mL at recurrence, 10 patients had supradiaphragmatic lesions in the lung and brain. None of the studied patients had bony metastasis at recurrence. Conclusion: In patients with suspected recurrence, extended-field CT to cover the thoracic region might be useful during follow-up of patients with ovarian cancer, regardless of CA 125 levels.